2019
DOI: 10.4149/bll_2019_083
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial toxicity of aluminium nanoparticles in comparison to its ionic form on isolated rat brain mitochondria

Abstract: The aim of this study was to evaluate the toxic effect of AlNPs on rat brain mitochondria and compare it with that of aluminium's ionic form. METHODS: Mitochondria were isolated from rat brain. Isolated mitochondria were treated with normal saline (Control) and different concentrations of aluminium ions (AlIs) and AlNPs (50, 100 and 200 μM). Then, the effect of AlNPs on electron transport chain complexes as well as various endpoints such as mitochondrial oxidative damage (reactive oxygen species, lipid peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Furthermore, AlCl 3 -associated mitochondrial damage was a prominent feature in the present study in Sertoli and Leydig cells, rounded spermatids, primary spermatocytes, spermatogonia, and spermatozoa. These findings were in agreement with those of Arab-Nozari et al (2019) and Skalny et al (2021).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, AlCl 3 -associated mitochondrial damage was a prominent feature in the present study in Sertoli and Leydig cells, rounded spermatids, primary spermatocytes, spermatogonia, and spermatozoa. These findings were in agreement with those of Arab-Nozari et al (2019) and Skalny et al (2021).…”
Section: Discussionsupporting
confidence: 92%
“…About 250 μL of the sample containing mitochondria was mixed with 750 μL of the swelling buffer (70 mM sucrose, 230 mM mannitol, 3 mM HEPES, 2 mM trisphosphate, 5 mM succinate, and 1 μM of rotenone). Then, the absorbance was read using an ELISA reader (Tecan, Rainbow Thermo, Austria) [22].…”
Section: Assessment Of Mitochondrial Swellingmentioning
confidence: 99%
“…Treatment of mitochondria (isolated from male Wistar rat brain tissue) with Al NPs increased ROS production, depleted GSH, increased lipid peroxidation, induced mitochondrial swelling, and induced the release of Cyt c, indicating mitochondrial mediated apoptosis [ 259 ]. Since complexes I and III are the main sources of ROS formed as a by-product in the ETC, Arab-Nozari et al (2019) [ 259 ] used substrates and inhibitors for ETC complexes I and III to determine that Al NPs were producing most of the ROS through inhibition of complex III [ 221 ].…”
Section: Effects Of Nanoparticles On Mitochondrial Functionmentioning
confidence: 99%
“…Cytochrome c is a heme protein in mitochondria that plays an essential role in the ETC and apoptosis [ 386 , 387 ]. Several studies have found upregulation of Cyt c in various cell lines and animal models, potentially due to apoptosis caused by NPs or by a different response [ 52 , 230 , 240 , 256 , 259 , 263 , 347 ]. A molecular dynamics (MD) simulation found that the adsorption of Cyt c to Si NPs was through hydrophobic interactions between key amino acid residues and the Si NPs resulting in structural stabilization.…”
Section: Nanoparticle–protein Interactionsmentioning
confidence: 99%